Study of Environmental Parameters in Gillnet Fishing Catchment area in Teluk Dalam Village Kuala Kampar Sub-District PelalawanDistrict Riau Province - Muhammad Habibi; Alit Hindri Yani; Usman Usman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
Abstract The purpose of this research is to obtain the condition data of environmental parameters of gillnet fishing gear area in TelukDalam Village in Kuala Kampar SubdistrictPelalawan Regency of Riau Province.            This research was carried out in February 2018, in TelukDalam Village in Kuala Kampar Subdistrict by direct observation and measurement in the field. The method used in this research is survey method, where the data obtained by observation and measurement directly in the field. Primary data measured include temperature, salinity, current velocity, brightness, depth, acidity (pH), and types of fish Gillnet catch. While the secondary data will be obtained from related institution in the form of tophografi and monographs Pelalawan District Riau Province. The method used in this research is survey method, where the data obtained by the village. The results of environmental parameters measurements are collected, tabulated into tabular form.            The results of the research have been conducted that from the measurement of environmental parameters carried out simultaneously when the fisherman made the arrest. Parameters measured during the research are: Temperature, Salinity, Brightness, Flow, Depth, and pH. Water conditions in TelukDalam have different characteristics. Based on the results of the field, it can be seen that the water temperature in the study area does not change every day ranging from 300C-310C, water salinity value ranges from 1.20 to 1.33 ppt, water brightness ranges from 28-30 cm, change the current velocity for 10 trip arrests within 10 days are in the range of 0.057-0.076 m / dt. The depth of the waters in the village of TelukDalam Kuala Kampar Sub-district ranges from 8 depa equals 14.4 meters. field measurements of pH values ranged from 5.8.            Based on the type of fish caught using gillnet fishing gear is 11.5kg shark, 40kg kurau, sea breeze 46.5kg, 72kg snapper and 66.5kg catfish. The average value of the catch was 23.65 kg for 10 days. Keywords: gillnet fishing gear, environmental parameters, fishing areas